Effects of different surface treatments on bond strength of an indirect composite to bovine dentin - Laiza Tatiana Poskus; Rosana Sampaio Meirelles; Victor Blunck Schuina; Liana Matos Ferreira; Eduardo Moreira da Silva; Jose Guilherme Antunes Guimarães (Wolters Kluwer Medknow Publications, 2015)
Background: Several surface treatments could be used to improve the bond strength (BS) between indirect composites and cement. Aim: To evaluate the BS of an indirect composite submitted to different surface treatments, cemented to bovine dentin. Settings and Design: One hundred and fifty conical cavities were prepared in slices of bovine dentin and bulk filled with the composite. Materials and Methods: After curing and removal from the cavity, the restorations were treated according to the groups (n = 10): C-untreated, S-Sandblasting; SS-Sandblasting + silane; F-hydrofluoric acid; FS-hydrofluoric acid + silane; SF-Sandblasting + hydrofluoric acid; SFS-Sandblasting + hydrofluoric acid + silane; E-ethanol; ES-ethanol + silane; SE-Sandblasting + ethanol; SES-Sandblasting + ethanol + silane; P-H2O2; PS-H2O2 + silane; SP-Sandblasting + H2O2; SPS-Sandblasting + H2O2 + silane. After cementation, push-out test was performed in a universal testing machine. Statistical Analysis: Data were submitted to nonparametric tests (Kruskal-Wallis and Mann-Whitney U-tests, α = 0.05). The failure mode was observed under a stereomicroscope and the topography by scanning electronic microscopy (SEM). Results: Sandblasted groups led to the highest BS values, (P < 0.001), except for the SFS group. SE, SES, and SPS led to higher BS values than S and SS groups (P < 0.05). F, E andPgroups showed the lowest BS values. The number of cohesive or mixed failures was related to higher BS values. SEM evaluation showed major irregularities only for sandblasted groups. Conclusions: Sandblasting was a safe surface treatment for the indirect composite, increasing the BS values. Hydrofluoric acid applied after sandblasting damaged the BS values and should not be recommended while ethanol and H2O2, when applied after sandblasting, were effective in increasing BS values.